2015
DOI: 10.1177/0017896915571144
|View full text |Cite
|
Sign up to set email alerts
|

Oral health promotion and homelessness: A theory-based approach to understanding processes of implementation and adoption

Abstract: Objective: To use the Theory of Diffusion of Innovations as a framework to explore the qualitative data gleaned from a process evaluation of the Smile4life intervention across Scottish National Health Service (NHS) Boards and to inform future oral health promotion and homelessness. Design: A qualitative exploration. Setting: In 2012, the Smile4life programme to promote the oral health of homeless people was launched in Scotland. Practitioners received training to ensure its successful implementation and adopti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…Dental professionals may fear aggression and have cross infection concerns with regard to their homeless patients . Limited or no training in dealing with socially excluded groups can affect the confidence of staff in dealing with homeless people …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Dental professionals may fear aggression and have cross infection concerns with regard to their homeless patients . Limited or no training in dealing with socially excluded groups can affect the confidence of staff in dealing with homeless people …”
Section: Resultsmentioning
confidence: 99%
“…Homeless people are sometimes refused ongoing care at dental practices and some clinics, or dentists are hesitant to accept homeless people for treatment . Reasons reported for precluding homeless people from “registering” or attending included lack of a fixed address (ie, having a hostel address), the practice being full, or existence of a waiting list, the practice taking only private patients and patients being on welfare benefits .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The evaluation found that it took NHS Boards an average of 16 months to implement the Smile4life intervention following the launch of the Guide for Trainers training package. The results of this evaluation highlighted various barriers to successful implementation, particularly a lack of resources (staffing, time constraints), and poor engagement between the NHS and the Third Sector [17]. Factors that facilitated implementation included motivated practitioners and a willingness to engage with other organisations [17].…”
Section: Introductionmentioning
confidence: 99%